FROM THE EXPERIENCE OF USING MODERN INFORMATION AND COMPUTER TECHNOLOGY IN LITERATURE CLASSES - Abdullaeva Barno, (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
The relevance of the article is determined by the introduction in the educational process of advanced pedagogical information and communication technologies. Informatization of society and education determines the need to use information and computer technology in school education. The use of modern information and computer technology at the lessons of literature is a response to the challenges of time and an effective means of increasing interest in the subject, deepening students' knowledge.